A Phosphine Functionalized β‐Diketimine Ligand for the Synthesis of Manifold Metal Complexes. Issue 58 (31st August 2020) - Zovko, Christina; Bestgen, Sebastian; Schoo, Christoph; Görner, Anne; Goicoechea, Jose M.; Roesky, Peter W.
Abstract: A bis(diphenyl)‐phosphine functionalized β‐diketimine (PNac‐H) was synthesized as a flexible ligand for transition metal complexes. The newly designed ligand features symmetrically placed phosphine moieties around a β‐diketimine unit, forming a PNNP‐type pocket. Due to the hard and soft donor atoms (N vs. P) the ligand can stabilize various coordination polyhedra. A complete series ranging from coordination numbers 2 to 6 was realized. Linear, trigonal planar, square planar, tetrahedral, square pyramidal, and octahedral coordination arrangements containing the PNac‐ligand around the metal center were observed by using suitable metal sources. Hereby, PNac‐H or its anion PNac − acts as mono‐, bi‐ and tetradendate ligand. Such a broad flexibility is unusual for a rigid tetradentate system. The structural motifs were realized by treatment of PNac‐H with a series of late transition metal precursors, for example, silver, gold, nickel, copper, platinum, and rhodium. The new complexes have been fully characterized by single crystal X‐ray diffraction, NMR, IR, UV/Vis spectroscopy, mass spectrometry as well as elemental analysis. Additionally, selected complexes were investigated regarding their photophysical properties. Thus, PNac‐H proved to be an ideal ligand platform for the selective coordination and stabilization of various metal ions in diverse polyhedra and oxidation states. Abstract : One‐size‐fits‐all : A β‐diketimine ligand and its corresponding anion, forming a PNNP‐type pocket, can stabilize various coordination polyhedral. A complete series of complexes forming seven different coordination polyhedral and coordination numbers ranging from 2 to 6 were realized.